Intestinal microbiome–rheumatoid arthritis crosstalk: The therapeutic role of probiotics - Opoku, Yeboah Kwaku; Asare, Kwame Kumi; Ghartey-Quansah, George; Afrifa, Justice; Bentsi-Enchill, Felicity; Ofori, Eric Gyamerah; Koomson, Charles Kwesi; Kumi-Manu, Rosemary (Frontiers in Microbiology, 2022)
Rheumatoid arthritis (RA) is a common systemic autoimmune disease with a global health importance. It is characterized by long-term complications, progressive disability and high mortality tied to increased social-economic pressures. RA has an inflammatory microenvironment as one of the major underlying factors together with other complex processes. Although mechanisms underlying the triggering of RA remain partially elusive, microbiota interactions have been implicated. Again, significant alterations in the gut microbiome of RA patients compared to healthy individuals have intimated a chronic inflammatory response due to gut dysbiosis. Against this backdrop, myriads of studies have hinted at the prospective therapeutic role of probiotics as an adjuvant for the management of RA in the quest to correct this dysbiosis. In this article, the major gut microbiome alterations associated with RA are discussed. Subsequently, the role of the gut microbiome dysbiosis in the initiation and progression of RA is highlighted. Lastly, the effect and mechanism of action of probiotics in the amelioration of symptoms and severity of RA are also espoused. Although strain-specific, probiotic supplementation as adjuvant therapy for the management of RA is very promising and warrants more research.